Synthesis of Carbon Microparticles from Red Dragon Fruit (Hylocereus undatus) Peel Waste and Their Adsorption Isotherm Characteristics - Asep Bayu Dani Nandiyanto; Rina Maryanti; Meli Fiandini; Risti Ragadhita; Dian Usdiyana; Sri Anggraeni; Wafa Raihana Arwa; Abdulkareem Sh. Mahdi Al-Obaidi (Molekul, 2020)
This study aims to demonstrate the preparation of carbon microparticles obtained from red dragon fruit peel waste and their adsorption isotherm characteristics. The carbon microparticles were prepared by combining carbonization (at 250°C) and saw-milling process, and to get carbon microparticles with a specific size, sieve analysis was used. The adsorption isotherm was done by testing the adsorption ability of carbon microparticles with a specific size into curcumin solution in the batch-type reactor. The adsorption results were then compared to several standard isotherm models (i.e., Langmuir, Freundlich, Temkin, and Dubinin-Radushkevich models) for understanding what phenomena happen during the adsorption process. The adsorption analysis was also confirmed by testing several sizes of the carbon microparticles to predict the proposal mechanism in the adsorption process. The analysis results showed that the multilayer adsorption process occurs for all sizes in the micrometer range, and the process involves physical interactions between adsorbate and surface of adsorbent. The existence of multilayers is due to the possibility in the existence of porous structure in the carbon microparticles. This study is important for giving an alternative solution for reusable organic waste as well as supporting the fundamental researches in the further applications of carbon particles as catalyst and adsorbent.